Alternative conceptions of obesity and perception of obese people amongst children. Issue 5 (19th October 2020) - Weissová, Monika; Prokop, Pavol
ABSTRACT: Children's ideas, which differ from a scientific view, are termed as alternative conceptions (AC). AC are extremely resistant to change and arise from everyday experience. Investigation of children's AC about weight gain and their ability to discriminate between healthy and unhealthy foods is important, because it can help teachers reduce obesity amongst children. We investigated these issues in a sample of kindergarten and primary school children in Slovakia. More AC about weight gain were found in primary school children, despite the fact that their abilities to discriminate between healthy and unhealthy foods were more sophisticated than the abilities of kindergarten children. These differences were not influenced by gender and what is important, primary school children more frequently correctly noticed that the amount of food, not the food quality itself, impacts the occurrence of obesity in humans compared with kindergarten children. We also found that children's perceptions of obese people are negative and unrelated to children's age or AC about weight gain and the ability to discriminate food. These results suggest that both alternative conceptions about weight gain and children's perception of obese people are unrelated to age, gender and abilities to discriminate between healthy and unhealthy food.